Screenprinting on textiles : the complete guide - Westergaard, Sue (Ramsbury, Marlborough : The Crowood Press Ltd, 2020)
Screenprinting is essentially a stencil method of printing, but is has vast potential. This beautiful book explains the techniques behind the art and introduces ideas to explore its exciting and versatile qualities
-- Introduction -- Printing on textiles -- the basics -- Designing for print -- Making screen stencils using autographic and low-tech techniques -- Making photo stencils -- Make ready and print -- Printing with colour -- Texture, shape and shine -- Print and play -- 'Ready-mades' -- Scale and repeat -- Embellish and finish -- What next?
Includes bibliographical references and index
Keywords: Serigraphy -- Technique; Textile printing -- Technique